ANISIO TEIXEIRA, THE MANAGEMENT AND FIRST CHALLENGES IN THE EDUCATION INSPECTORATE AT BAHIA (1924-1929) - Cassol Carbello, Sandra Regina [UNESP]; Ribeiro, Ricardo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This work is part of research project under development in the doctorate school in education, which highlights the contributions of Anisio Teixeira for the organization of the Brazilian public school. To this text, we selected the actions taken during his first experience in education, when he assumed the Education Inspectorate at Bahia in 1924. This is a bibliographic study anchored in the author's own records and other intellectuals who devoted themselves to his legacy. The results point to the reorganization of shares of primary school with the development of an educational program and redefinition of your goals and methods, concomitantly, stresses the need for professionalization and teacher training to carry out the reform undertaken.
Keywords: Primary school; Public school; Teacher training